Career Advancement: The Experiences of Minority Nurses in Accessing Leadership Positions in a Tertiary Care Setting - Naima Bouabdillah; Amélie Perron; Dave Holmes (York University Libraries, 2021)
Minority nurses are underrepresented in leadership roles in the Canadian healthcare system. The purpose of this study was to explore MNs' perceptions and experiences with regards to career development and MNs in leadership positions. Twelve nurses, four Caucasian and eight from the Caribbean and Africa in a tertiary care setting were recruited through purposive sampling. Face-to-face semi-structured interviews were conducted, transcribed, coded, and analyzed using critical ethnography. Findings revealed lack of social support, of equal opportunities, of recognition and of trust. Despite negative experiences, minority nurses recognized the value of their work experience at the hospital where they were employed. Committing to a diverse workforce in leadership roles can ultimately have an effect on patient care. Minority nurses' leadership is needed to provide role models and to ensure the delivery of competent care to diverse populations.